Studi Takhrij dan Syarah Hadis tentang Puasa Ramadhan - Ihsan Fauzi (Gunung Djati Conference Series, 2023)
This study aims to discuss the hadith about Ramadan fasting. This study uses a qualitative approach by applying a descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about fasting, in the history of al-Bukhari No. 37. The results and discussion of this study indicate that the quality of the status of hadith is shahih li dzatihi. This study concludes that the hadith narrated by al-Bukhari No. 37 is maqbul ma'mul bih which is relevant to be used as motivation in carrying out Ramadan fasting.